In Vitro Antimicrobial Susceptibilities of Francisella tularensis subsp. holarctica Isolates from Tularemia Outbreaks That Occurred from the End of the 20th Century to the 2020s in Spain - Sonia Martínez-Martínez; Elías-Fernando Rodríguez-Ferri; David Rodríguez-Lázaro; Marta Hernández; José-Ignacio Gómez-Campillo; María del Carmen Martínez-Nistal; María-Isabel Fernández-Natal; María-José García-Iglesias; Olga Mínguez-González; César-Bernardo Gutiérrez-Martín (Antibiotics, 2021)
A collection of 177 Francisella tularensis subsp. holarctica clinical isolates (29 from humans and 148 from animals, mainly hares and voles) was gathered from diverse tularemia outbreaks in the Castilla y León region (northwestern Spain) that occurred from the end of the 20th century to the 2020s. Along with four F. tularensis subsp. holarctica reference strains, all of these clinical isolates were tested using a broth microdilution method to determine their susceptibility to 22 antimicrobial agents, including β-lactams, aminoglycosides and one member each of the tetracycline, glycylcycline, quinolone and sulphonamide classes. Many multi-resistance profiles were found among the tested isolates, but especially among those of human origin (all but two isolates showed resistance to at least 13 of 18 antimicrobial agents). Even so, all human isolates were susceptible to gentamicin and tobramycin, while more than 96% of animal isolates were susceptible to these two aminoglycosides. Ciprofloxacin showed activity against more than 92% of animal and human isolates. However, almost 21% of human isolates were resistant to tetracycline, and more than 65% were resistant to tigecycline. Finally, a quite similar activity to other F. tularensis subsp. holarctica isolates collected 20 years earlier in Spain was observed.